2007
DOI: 10.1007/s10620-006-9432-6
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Localization in Young Patients: Should We Expand the Screening Program?

Abstract: We sought to investigate the frequency and distribution of colorectal cancer (CRC) in patients by age and to evaluate whether there is a difference between young (<40 years of age) and older patients ( > or = 40 years of age) with regard to cancer localizations. From a total of 5165 colonoscopies, 314 (6.0%) cases were identified to have colorectal carcinoma. Forty-one (13%) of 314 CRC patients were young, with a mean age of 31.1 +/- 5.7 years. When cancer localizations were compared with reference to age, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…In our study, the proportion of patients who were less than 40 years-of-age was 11%. This proportion in a Turkish study was 13% (Savas et al, 2007). Recent studies in Indian population showed that even within a country, this proportion might highly vary from 12.6% to 39% (Nath et al, 2009;Peedikayil et al, 2009;Gupta et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…In our study, the proportion of patients who were less than 40 years-of-age was 11%. This proportion in a Turkish study was 13% (Savas et al, 2007). Recent studies in Indian population showed that even within a country, this proportion might highly vary from 12.6% to 39% (Nath et al, 2009;Peedikayil et al, 2009;Gupta et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…[5][6][7][8][9] Other reports have found an equivalent or better cancer-specific survival rates in young patients compared with older patients despite presenting with advanced stage disease. 8,10 The limited literature data are also conflicting with regards to the more common locations of colorectal carcinoma, with some indicating increased frequency of proximal right-sided colorectal carcinoma 11 while others demonstrating increased frequency of rectal and rectosigmoid carcinoma. 3,12 Most of the published data are confounded by inclusion of hereditary colorectal carcinoma, particularly Lynch syndrome-associated colorectal carcinomas, which have differing genetic events leading to tumorigenesis and often have improved survival compared with non-syndromic colorectal carcinoma.…”
mentioning
confidence: 99%
“…Previous studies underlined the significance of heritance as an indicator of EOCRC [11,12] . Supporting these views, early-onset and hereditary forms of CRC demonstrate similar well-known pathological features [11,13] . Nevertheless, the current knowledge is that EOCRC is a heterogeneous disease with both familial and sporadic cases.…”
Section: Molecular Pathogenesis Of Eocrcmentioning
confidence: 63%
“…These tumors are pathologically recognized with lowgrade tumor differentiation, mucinous component and high signet ring cells frequency [11,13] . Polyp development is contently observed during the follow-up period of EOCRC [10] .…”
Section: Molecular Pathogenesis Of Eocrcmentioning
confidence: 99%